UMP celebrates industry’s contribution with an appreciation night - UMP, PNC
Universiti Malaysia Pahang (UMP) held, for the first time ever, a UMP-Industry Appreciation Dinner & Award Night, in a show of appreciation to the various industries which have contributed to the university’s academic development programme, research collaboration and product commercialization, as well as industrial training placements.